Exploring the enzyme‐catalyzed synthesis of isotope labeled cyclopropanes. (2nd February 2022) - Sardana, Malvika; Mühlfenzl, Kim S.; Wenker, Sylvia T. M.; Åkesson, Christian; Hayes, Martin A.; Elmore, Charles S.; Pithani, Subhash
Abstract : Cyclopropanes are commonly employed structural moieties in drug design since their incorporation is often associated with increased target affinity, improved metabolic stability, and increased rigidity to access bioactive conformations. Robust chemical cyclopropanation procedures have been developed which proceed with high yield and broad substrate scope, and have been applied to labeled substrates. Recently, engineered enzymes have been shown to perform cyclopropanations with remarkable diastereoselectivity and enantioselectivity, but this biocatalytic approach has not been applied to labeled substrates to date. In this study, the use of enzyme catalysis for the synthesis of labeled cyclopropanes was investigated. Two readily available enzymes, a modified CYP450 enzyme and a modified Aeropyrum pernix protoglobin, were investigated for the cyclopropanation of a variety of substituted styrenes. For this biocatalytic transformation, the enzymes required the use of ethyl diazoacetate. Due to the highly energetic nature of this molecule, alternatives were investigated. The final optimized cyclopropanation was successfully demonstrated using n ‐hexyl diazoacetate, resulting in moderate to high enantiomeric excess. The optimized procedure was used to generate labeled cyclopropanes from 13 C‐glycine, forming all four labeled stereoisomers of phosphodiesterase type‐IV inhibitor, MK0952. These reactions provide a convenient and effective biocatalytic route to stereoselective 13 C‐labeled cyclopropanes and serve as a proof‐of‐concept for generating stereoselective labeled cyclopropanes. Abstract : Cyclopropanes are commonly employed structural moieties in drug design. In this study, the use of enzyme‐catalysis for the synthesis of labeled cyclopropanes was investigated. Two readily available (modified) enzymes were studied for the cyclopropanation of substituted styrenes with ethyl diazoacetate. This diazoacetate is highly energetic; therefore, alternatives were investigated. The final optimized cyclopropanation was successfully demonstrated using n‐hexyl diazoacetate and used to synthesize stereoselective 13C‐labeled cyclopropanes. This optimized procedure serves as a proof‐of‐concept for generating stereoselective‐labeled cyclopropanes.